√49+√25-4√0,25 = (√109 – √121 – √81): √0,49= √1/9 . √0,81.√0,09= 3/5 .√16 + 2. √16/25

Question

√49+√25-4√0,25 =
(√109 – √121 – √81): √0,49=
√1/9 . √0,81.√0,09=
3/5 .√16 + 2. √16/25

in progress 0
Everleigh 5 ngày 2021-09-09T13:55:58+00:00 2 Answers 2 views 0

Answers ( )

    0
    2021-09-09T13:57:24+00:00

    ` \sqrt49 + \sqrt25 – 4\sqrt(0,25)`

    `= 7 + 5 – 2`

    `= 10`

    `(\sqrt109 – \sqrt121 – \sqrt81) : \sqrt(0,49)`

    `= (\sqrt109 – 11 – 9) : 0,7`

    `= (\sqrt109 – 20) : 0,7`

    `= (10\sqrt109)/7 – 200/7`

    `= (10\sqrt109 – 200)/7`

    `\sqrt(1/9) . \sqrt(0,81) . \sqrt(0,09)`

    `= 1/3 . 0,9 . 0,3`

    `= 0,09`

    `3/5 . \sqrt16 + 2\sqrt(16/25)`

    `= 3/5 . 4 + 2. 4/5`

    `= 12/5 + 8/5`

    `= 4`

    0
    2021-09-09T13:57:52+00:00

    $\sqrt{49}+\sqrt{25}-4.\sqrt{0,25}$

    $= 7+5-4.0,5$

    $= 7+5-2=10$

    $(\sqrt{109}-\sqrt{121}-\sqrt{81}):\sqrt{0,49}$

    $=(\sqrt{109}-11-9):0,7$

    $= (\sqrt{109}-20):0,7$

    $= \dfrac{10(\sqrt{109}-20)}{7}$

    $\sqrt{\frac{1}{9}}.\sqrt{0,81}.\sqrt{0,09}$

    $=\frac{1}{3}.0,9.0,3$

    $= 0,09$

    $\frac{3}{5}.\sqrt{16}+2\sqrt{\frac{16}{25}}$

    $=\frac{3}{5}.4+2.\frac{4}{5}$

    $=\frac{12}{5}+\frac{8}{5}$

    $=4$

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )